Detection of serum soluble markers of immune activation in rheumatoid arthritis - T. Kogure; T. Itoh; Y. Shimada; T. Shintani; H. Ochiai; K. Terasawa (Mediators of Inflammation)
The mutual correlation among soluble CD4 (sCD4), soluble CD8 (sCD8), and soluble CD23 (sCD23) has not yet been studied in patients with rheumatoid arthritis (RA), although previous studies have demonstrated that certain soluble markers of immune activation are elevated in RA. Thus, we examined this correlation based on the serum levels of sCD4, sCD8 and sCD23, and that of their levels with other serum markers such as immunoglobulin (Ig) subtypes (IgG, IgM and IgA), IgM-rheumatoid factor (IgM-RF) and C-reactive protein (CRP) in 25 RA patients, sCD4 was not elevated, whereas both sCD8 and sCD23 increased in RA patients compared with the healthy controls; a majority of RA patients, in particular, showed a high sCD23 level. The level of sCD23 showed a correlation with that of IgM-RF, but not with those of IgG, IgM, IgA and CRP. Importantly, a high level of sCD23 was not always accompartied with that of sCD8. The independent change between sCD23 and sCD8 levels was also observed in a one-year follow-up study of the two RA patients. These findings indicate that B cells might be generally activated in RA, whereas T-cell activation in variable in each patient with RA, suggesting that sCD23 is a more indicative marker for the immune status of RA patients than sCD8 from the clinical aspects.